214 DCE-MRI in neurological disease: how to do it. Issue 6 (27th May 2022) - Varatharaj, Aravinthan; Darekar, Angela; Cramer, Stig P; Larsson, Henrik BW; Galea, Ian
Abstract : MRI with gadolinium-based contrast agent is widely used in clinical practice and is a key tool for the diagnosis and monitoring of diseases such as multiple sclerosis. Dynamic contrast-enhanced MRI (DCE-MRI) is an advanced technique which maps the time course of T1 signal enhancement. Quantitative informa- tion regarding tissue properties can be extracted, providing additional utility compared to conventional contrast MRI. No further contrast injection is required, and the impact on total scan time can be minimal. Maps of blood-brain barrier permeability can be produced, with an ability to detect leakage well below the threshold of conventional MRI. This practical poster outlines a step-by-step protocol for setting up brain DCE-MRI, analysing the data with minimal user input, and incorporating it into research and future clinical practice. Common pitfalls and their solutions are addressed. The information is not vendor-specific so can easily be applied to any MR hardware. a.varatharaj@soton.ac.uk